2019
DOI: 10.1186/s12887-019-1435-5
|View full text |Cite
|
Sign up to set email alerts
|

Hb Knossos (HBB: c.82G > T), β-globin CD 5 (−CT) (HBB: c.17_18delCT) and δ-globin CD 59 (−a) (HBD: c.179delA) mutations in a Syrian patient with β-thalassemia intermedia

Abstract: Background Beta thalassemia (β-thal) is an inherited hemoglobin disorder characterized by reduced synthesis of the hemoglobin that results in microcytic hypochromic anemia. β-Thalassemia intermedia (TI) is a clinical term of intermediate gravity between the carrier state and β-thalassemia major (β -TM). Case presentation We describe a 12-year-old male proband originating from Al-Quneitra province - southwest Syria. Hematological investigations revealed, pallor and anemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(27 reference statements)
0
2
0
1
Order By: Relevance
“…In case of variant 13, when the molecular analysis result indicated beta-thalassemia caused by a nonsense mutation in HBB, the peak in zone D and the decreased HbA2 concentration could only be explained if the patient also carried a mutation in HBD. Faten, et al [16] reported a similar case in 2019, in which the proband was affected by beta-thalassemia intermedia and also had a mutation in HBD, resulting in an electrogram indicating a low HbA2 concentration. We did not have the appropriate tools to analyze the HBD gene; thus, the presence of an HBD variant could not be verified.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In case of variant 13, when the molecular analysis result indicated beta-thalassemia caused by a nonsense mutation in HBB, the peak in zone D and the decreased HbA2 concentration could only be explained if the patient also carried a mutation in HBD. Faten, et al [16] reported a similar case in 2019, in which the proband was affected by beta-thalassemia intermedia and also had a mutation in HBD, resulting in an electrogram indicating a low HbA2 concentration. We did not have the appropriate tools to analyze the HBD gene; thus, the presence of an HBD variant could not be verified.…”
Section: Discussionmentioning
confidence: 98%
“…Faten, et al . [ 16 ] reported a similar case in 2019, in which the proband was affected by beta-thalassemia intermedia and also had a mutation in HBD , resulting in an electrogram indicating a low HbA 2 concentration. We did not have the appropriate tools to analyze the HBD gene; thus, the presence of an HBD variant could not be verified.…”
Section: Discussionmentioning
confidence: 99%
“…При представения клиничен случай 1 лабораторни данни за таласемия минор има само при единия родител, докато клиниката на пациента (включително нуждата от хемотрансфузии) не кореспондира с носителски статус. Разкритото с генетичен анализ носителство на HbKnossos при другия родител не се асоциира с клинична симптоматика и не води до промяна в лабораторните показатели от електрофорезата на хемоглобин, което е в съответствие с докладваното в различни бази данни [11][12][13]. Провеждането на генетични изследвания при пробанда и родителите е препоръчително във всички случаи на бета-таласемия и особено полезно при пациенти с нетипична клиника.…”
Section: обсъжданеunclassified